1979
DOI: 10.1021/ac50042a026
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced photoacoustic spectroscopy of some rare earth ions in aqueous solutions

Abstract: region by using dye lasers in conjunction with argon ion and krypton ion lasers. In the future and with the advent of lasers encompassing all wavelengths including the UV region, LIPAS should become a powerful tool for ultratrace analysis. ACKNOWLEDGMENTOne of the authors (M. N.) is indebted to Keiichi Furuya of the Science University of Tokyo for his encouragement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In addition to high instrumental sensitivity, thermooptical spectroscopy is characterised by having a substantially smaller dependence on light scattering and the possibility of detecting trace amounts of elements in samples. It should be noted that a photothermal spectrum does not coincide with the corresponding classical absorption spectrum (in particular, in the case of rare-earth metals), 412 which provides the basis for developing more selective and sensitive procedures for the detection of trace amounts of compounds. For example, procedures were designed to detect uranium(VI), neodymium(III) and praseodymium(III) at a level of 10 76 ± 10 75 mol litre 71 (Refs 24,30,413,414).…”
Section: Use Of Spectrophotometric Proceduresmentioning
confidence: 99%
“…In addition to high instrumental sensitivity, thermooptical spectroscopy is characterised by having a substantially smaller dependence on light scattering and the possibility of detecting trace amounts of elements in samples. It should be noted that a photothermal spectrum does not coincide with the corresponding classical absorption spectrum (in particular, in the case of rare-earth metals), 412 which provides the basis for developing more selective and sensitive procedures for the detection of trace amounts of compounds. For example, procedures were designed to detect uranium(VI), neodymium(III) and praseodymium(III) at a level of 10 76 ± 10 75 mol litre 71 (Refs 24,30,413,414).…”
Section: Use Of Spectrophotometric Proceduresmentioning
confidence: 99%
“…The first systematic investigation of PA’s suitability for absorption measurements in liquids was reported by Tam et al in 1979 who applied a pulsed laser to generate the PA effect. Later, several other groups investigated the possibilities of the PA techniques mostly with modulated rather than pulsed laser sources (see, e.g., refs and ). A direct comparison of pulsed versus modulated PA was given by Atalar .…”
mentioning
confidence: 99%
“…Here, we present a direct evidence of anomalous temporal cooling effect of aqueous E u 3 solution by pulsed photoexcitation, which is thought to originate from the slow nonradiative decay of the excited E u 3 . This effect was not observed when cw photoacoustic method was employed (3). We found that the magnitude of the photoacoustic signal from the aqueous Eu3+ solution became smaller than that of neat water in case the dye laser wavelength was tuned to the transition from the 7F1 state to the 5D0 state of E u 3 ion.…”
Section: Introductionmentioning
confidence: 74%